If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = x + 27 Reorder the terms: 3(-1 + 2x) = x + 27 (-1 * 3 + 2x * 3) = x + 27 (-3 + 6x) = x + 27 Reorder the terms: -3 + 6x = 27 + x Solving -3 + 6x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 6x + -1x = 27 + x + -1x Combine like terms: 6x + -1x = 5x -3 + 5x = 27 + x + -1x Combine like terms: x + -1x = 0 -3 + 5x = 27 + 0 -3 + 5x = 27 Add '3' to each side of the equation. -3 + 3 + 5x = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 27 + 3 5x = 27 + 3 Combine like terms: 27 + 3 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 | | 9a-8+6a-4= | | 2(3-8)+7= | | y=-5+4sinx | | (5)+(-14)= | | f(x)=-0.91666667*x+1.5 | | (11)+(-3)= | | 6/5cos-1(y/8)=pi | | 16x^6-10x^4/2x^3 | | x-(5x+2)=-4(x-3) | | (-9)+-(14)= | | -x/2*x | | (15)+(-10)= | | 19(8x+3)= | | 5x-(3x+7)=9+2(x-8) | | ax+bx+6=0 | | x=40-2x |